2004
DOI: 10.1152/ajpcell.00444.2003
|View full text |Cite
|
Sign up to set email alerts
|

MEF2 activation in differentiated primary human skeletal muscle cultures requires coordinated involvement of parallel pathways

Abstract: The myocyte enhancer factor (MEF)2 transcription factor is important for development of differentiated skeletal muscle. We investigated the regulation of MEF2 DNA binding in differentiated primary human skeletal muscle cells and isolated rat skeletal muscle after exposure to various stimuli. MEF2 DNA binding activity in nonstimulated (basal) muscle cultures was almost undetectable. Exposure of cells for 20 min to 120 nM insulin, 0.1 and 1.0 mM hydrogen peroxide, osmotic stress (400 mM mannitol), or 1.0 mM 5-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…Compound C was developed as a selective inhibitor of AMPK [35] and it has been used in several studies to decipher cellular effects of AMPK [36][37][38]. Inhibition of AMPK by Compound C was evident in both hippocampal neurons and SH-SY5Y cells by its reduction of the phenformin-induced phosphorylation of ACC, a prototypical AMPK substrate commonly used as an indicator of AMPK activation [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound C was developed as a selective inhibitor of AMPK [35] and it has been used in several studies to decipher cellular effects of AMPK [36][37][38]. Inhibition of AMPK by Compound C was evident in both hippocampal neurons and SH-SY5Y cells by its reduction of the phenformin-induced phosphorylation of ACC, a prototypical AMPK substrate commonly used as an indicator of AMPK activation [28].…”
Section: Discussionmentioning
confidence: 99%
“…To test if AMPK activation by phenformin was responsible for the dephosphorylation of Akt and GSK3, cells were treated with the selective AMPK inhibitor Compound C [35].Forthese experiments, differentiated hippocampal neurons were treated with a higher concentration of Compound C (40 mM) than the generally used 10-20 mM concentrations [35][36][37][38] because in preliminary concentration-response experiments the lower concentrations of Compound C only slightly inhibited AMPK in these cells (data not shown). Pretreatment with 40 mM Compound C reduced the phenformin-induced increase in the phosphorylation of ACC at Ser79 (Fig.…”
Section: Phenformin Treatment Activates Ampk and Reduces The Phosphormentioning
confidence: 99%
“…In skeletal muscle, activated AMPK has been demonstrated to increase GLUT4 protein level and translocation [21,49,50] via MEF2 [25,27,48] . However, the findings in adipose tissue are controversial.…”
Section: Wwwchinapharcom Feng L Et Almentioning
confidence: 99%
“…Activated AMPK stimulates GLUT4 expression [20] and basal GLUT4 translocation in both skeletal muscle and adipocytes [21][22][23][24] . Moreover, studies in cardiac and skeletal muscle have found that AMPK regulates GLUT4 in a manner dependent upon a heterodimer of MEF2A and MEF2D (myocyte enhancer factor 2) [25][26][27] , a complex that can bind to the human GLUT4 promoter [26] and thus regulate GLUT4 transcription.…”
Section: Introductionmentioning
confidence: 99%
“…The GLUT4 MEF2 site (−473/−464) is required for tissue-specific and hormonal/ metabolic regulation of glucose transporters [15], providing a link between this transcription factor and GLUT4 regulation. MEF2A, MEF2C and MEF2D isoforms, but not the MEF2B isoform, are expressed in skeletal muscle and heart [16,17], and functional differences among the MEF2 isoforms exist [18]. In skeletal muscle and heart of diabetic mice, MEF2 DNA-binding activity is substantially reduced and correlated with a decrease in GLUT4 transcription rate.…”
Section: Introductionmentioning
confidence: 99%